Rewriting Buddhism : Pali Literature and Monastic Reform in Sri Lanka, 1157–1270 - Gornall, Alastair (Book collections on Project MUSE., 2020)
Rewriting Buddhism is the first intellectual history of premodern Sri Lanka's most culturally productive period.